Multicenter Placebo-Controlled Randomized Study of Ethyl Pyruvate in Horses Following Surgical Treatment for ≥ 360° Large Colon Volvulus - Johnson, Lindsey M.; Holcombe, Susan J.; Shearer, Tara R.; Watson, Victoria; Gandy, Jeffery; Southwood, Louise L.; Lynch, Tymothy M.; Schroeder, Eric L.; Fogle, Callie A.; Sordillo, Lorraine M. (Frontiers in Veterinary Science, 2020)
Identifying therapies that mitigate ischemic colonic injury and improve mucosal healing and intestinal viability are crucial to improving survival in horses with ≥ 360° large colon volvulus (LCV). Ethyl pyruvate is the ethyl ester of pyruvate with diverse pharmacologic effects that limit ischemic injury and hasten intestinal mucosal repair in preclinical rodents, sheep and swine models. The objective of this study was to determine the effects of ethyl pyruvate on systemic indices of colon viability, expression of inflammatory genes in whole blood, morbidity and survival after surgical correction of LCV compared to controls. Horses received either 150 mg/kg ethyl pyruvate in 1 liter lactated Ringer’s solution (LRS) or 1 liter LRS intravenously (IV) every 6 hours for 24 hours following surgical recovery for correction of LCV. Colic duration, perioperative heart rate (HR), packed cell volume (PCV), total solids (TS), blood L-lactate concentration, surgical time, intraoperative episodes of hypoxemia and hypotension, expression of inflammatory cytokine genes, fecal consistency and survival to hospital discharge were compared between ethyl pyruvate treated horses and controls. Twenty-two horses, 12 receiving ethyl pyruvate and 10 controls, were enrolled in the study. Ethyl pyruvate was safely administered to horses following surgical correction of LCV. No significant effects of ethyl pyruvate on post-operative variables, including survival, were found. Seven of 12 ethyl pyruvate treated horses and 5/10 controls survived to hospital discharge. Higher HR, PCV and blood L-lactate concentration at the time of hospital admission, P = 0.005, 0.01, 0.04, respectively, 24 hours after surgery, P = 0.001, 0.03, 0.02, respectively, were associated with death. Heart rate, P = 0.005, 48 hours after surgery was associated with death. Ethyl pyruvate was safely administered to horses following correction of LCV with no apparent adverse events but was not associated with improved post-operative outcomes including survival. A larger, randomized control trial is needed to fully evaluate the effectiveness of ethyl pyruvate. A major limitation of this investigation is the small sample size, making the study underpowered and creating a high possibility of type II error.